INDEPENDENT COMMISSIONERS MODERATE THE EFFECT OF LEVERAGE AND TRANSFER PRICING ON TAX AVOIDANCE - Triana Murtiningtyas; Elisabeth Cylvia Goba Fernandez; Sa'adah, Lailatus (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This research aims to analyze the effect of leverage and transfer pricing on tax avoidance with independent commissioners as moderating variables. The population used in this research is Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) in 2021-2023. The sampling method in this research used purposive sampling according to predetermined criteria and the number of samples used was 78 samples. The analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that leverage has an effect on tax avoidance, transfer pricing has no effect on tax avoidance, independent commissioners are unable to moderate the effect of leverage on tax avoidance and independent commissioners are unable to moderate the effect of transfer pricing on tax avoidance.